Total communication and technologies to interact with people with severe intellectual disability addressed to train healthcare, education and interpreting professionals - Postigo-Pinazo, Encarnación (My University, 2018)
Most of the programs and systems created to help disabled people are targeted to subjects who have certain abilities. People with severe intellectual disability are really at risk of being the most ignored since approaches devoted to cater for successful communication are not generally present in their everyday life scenarios. EC+ European project developed a mobile app to cater for the communication with this group of subjects and to empower professionals from various disciplines with the necessary tools (scientific materials on syndrome characteristics and intervention, multimodal resources and sign language) when they need to interact with intellectually disabled subjects in their professional environments. The interdisciplinary approach of total communication adopted as methodology for the EC+ project proved to have a promising outcome with different professionals.
Ponencia donde se exponen los resultados del proyecto europeo EC+ https://ecplusproject.uma.es/node/1
Keywords: Traducción - Innovaciones tecnológicas; Discapacitados; Apps; Interpreting; Education; Healthcare; Total communication